Kesejahteraan Psikologis Anak Rantau: Pentingnya Peran Orang Tua dalam Mendukung Melalui Teknologi Jarak Jauh - Zatayumni, Safirah Irda; Siregar, Mhd. Fuad Zaini (Ability: Journal of Education and Social Analysis, 2024)
The role of parents in supporting regional children emotionally through long-distance communication has a significant impact on children's psychological well-being. Proper emotional support, positive communication, and assistance in overcoming difficulties are important aspects that can help regional children adapt to new environments. Without the physical presence of parents, children in the region are at risk of experiencing various negative psychological impacts, including insecurity, difficulties in identity formation, and lack of emotional support. However, technology and communication media play an important role in maintaining the relationship between parents and regional children separated by distance. Therefore, it is important for parents to build open communication, provide emotional support, and be actively involved in the lives of their children to ensure optimal psychological well-being amid wandering challenges. This research uses a qualitative approach to explore the impact of remote communication between parents and children in the region on the psychological well-being of children in the region.